Exploring Sufistic Morality in A.R. Fachrudin’s Light Questions and Answers as Educational Material for Didactic Story Writing - Abdul Latif; Vismaia S Damaianti; Yeti Mulyati (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study aims to explore the Sufistic values found in Soal Jawab yang Ringan-Ringan (Light Questions and Answers) by A.R. Fachrudin, a prominent Islamic preacher and Muhammadiyah leader from 1968 to 1990. The research emphasizes the educational relevance of these values, particularly their application in moral and character education through literature. A descriptive qualitative method was used, focusing on textual analysis rather than numerical data. The data consisted of written discourse, field notes, personal documents, and other official records. The analysis involved data reduction, presentation, interpretation, and verification. The semiotic approach was employed to identify the symbolic representations of Sufistic values within the text. The findings reveal that A.R. Fachrudin's writings convey key aspects of moral Sufism, including repentance (taubah), fear and hope (khauf and raja'), asceticism (zuhud), poverty (faqr), patience (sabr), contentment (ridha), and constant awareness of God (muraqabah). These values are categorized as "index" signs in semiotic analysis, indicating their observable and practical manifestations in daily behavior. The Sufistic values expressed in Fachrudin’s work hold significant educational potential, especially for moral instruction in literary contexts. These values can be effectively integrated into writing and literature curricula, such as through the creation of didactic short stories. The study suggests that incorporating spiritual and ethical dimensions into education can enhance students' moral development and engagement with religious texts in meaningful, reflective ways.